2017
DOI: 10.1002/ajcp.12156
|View full text |Cite
|
Sign up to set email alerts
|

Youth Homelessness and Vulnerability: How Does Couch Surfing Fit?

Abstract: Youth homelessness is a problem characterized by high levels of vulnerability. The extent to which couch surfing - moving from one temporary housing arrangement to another - is part of youth homelessness is not well understood. Chapin Hall's Voices of Youth Count, a national research initiative, involves a multicomponent approach to studying youth homelessness. This study reports emerging findings regarding couch surfing and homelessness primarily from a national survey of 13,113 adults with youth ages 13-25 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 6 publications
0
25
0
Order By: Relevance
“…Still, a sizable share of the overall prevalence rates also involved couch surfing only without a safe and stable living arrangement. These experiences likely include a wide range of degrees of vulnerability (from lower-risk experiences of leveraging social networks during periods of housing instability to high-risk or exploitative arrangements) [ 15 , 24 ]. Additionally, some couch surfing could function as a precursor to more entrenched homelessness [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Still, a sizable share of the overall prevalence rates also involved couch surfing only without a safe and stable living arrangement. These experiences likely include a wide range of degrees of vulnerability (from lower-risk experiences of leveraging social networks during periods of housing instability to high-risk or exploitative arrangements) [ 15 , 24 ]. Additionally, some couch surfing could function as a precursor to more entrenched homelessness [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The policy commentary is followed by two brief reports on the prevalence of housing instability and homelessness among families being investigated for child maltreatment (Farrell, Dibble, Randall & Britner, ) and couch surfing among young people (Curry et al., ). Farrell, Dibble et al.…”
Section: Summaries Of Contributions In Contextmentioning
confidence: 99%
“…Using data from a nationally representative household telephone survey (over 13,000 adults with youth ages 13–25 in their households or themselves ages 18–25), Curry and her colleagues in the Voices of Youth Count study found couch surfing to be relatively common, particularly among the older age group (Curry et al., ). Among households with 13‐ to 17‐year‐olds and 18‐ to 25‐year‐olds, 4.0% and 20.5% (respectively) couch surfed in the preceding 12 months.…”
Section: Summaries Of Contributions In Contextmentioning
confidence: 99%
“…Curry et al. () explore the prevalence of couch surfing among adolescents. Additional findings of the Voices of Youth Count will serve to illuminate the link between homelessness and involvement in child welfare (Chapin Hall at the University of Chicago, n.d.).…”
Section: Translating Research To Housing Policymentioning
confidence: 99%